Expression of Repressor Element 1 Silencing Transcription Factor (REST) in Serotonin Neurons in the Adult Male Nile Tilapia (Oreochromis niloticus) - Soga, Tomoko; Nakajima, Shingo; Parhar, Ishwar S. (Frontiers in Neuroanatomy, 2021)
Repressor element-1 silencing transcription factor (REST) is highly expressed in the dorsal raphe where serotonin (5-hydroxytryptamine, 5-HT) neurons are located. REST works as a transcription factor for 5-HT receptor and tryptophan hydroxylase two gene expression. We hypothesized that REST is co-expressed in 5-HT neurons, which, if demonstrated, would be useful to understand the mechanism of 5-HT dysfunction-related disorders such as negative emotions and depression. Therefore, the present study was designed to examine the expression of REST gene in the brain (forebrain, midbrain, hindbrain) of adult male Nile tilapia (Oreochromis niloticus) using rt-PCR. Besides, using immunocytochemistry, co-localization of REST gene was examined in 5-HT neurons and with neuronal-/glial-cell markers. We found high expression of REST gene in the midbrain, region of the dorsal raphe, an area of 5-HT neurons. Double-label immunocytochemistry showed neuron-specific expression of REST co-localized in 5-HT neurons in the dorsal and ventral parts of the periventricular pretectal nucleus, paraventricular organ, dorsal and medial raphe nucleus. Since midbrain 5-HT neurons express REST, we speculate REST may control 5-HT neuronal activity related to negative emotions, including depression.